Selective isolation of Actinomycetes from mangrove sediment of Tanjung Lumpur, Kuantan, Malaysia - Mohamad, Nur Hanisah; Khan Chowdhury, Ahmed Jalal; Zainal Abidin, Zaima Azira (Malaysian Society for Microbiology, 2015)

(untitled)
Aims: Mangroves of Tanjung Lumpur, Kuantan, Pahang is considered as a relatively underexplored resource of actinomycetes. Based on the above perspective, a study was conducted on mangrove sediments of Tanjung Lumpur, Kuantan to isolate potential actinomycetes using several pretreatments and various selective media. Methodology and results: Sediments from five different sites at Tanjung Lumpur mangrove were collected and selectively pre-treated. The pretreated sediments were diluted and plated onto eight different selective media. A total of 172 potential actinomycetes were isolated from all the media. Antimicrobial activities of 61 selected strains were checked against 8 test microorganisms using cross streak method. Pretreatment of wet heat with seawater was the most effective method for the isolation of actinomycetes as it yielded a maximum of 105 actinomycete isolates and IM7 was the most suitable medium for actinomycete isolation with highest percentage of recovery (31 %). Forty three isolates (70.5 %) showed antimicrobial activities against one or more test microorganisms. Isolates IIUM B21 and IIUM B31 showed antimicrobial activity against all test microorganisms. Seven isolates showed antifungal activity as they inhibited only C. albicans. Ten isolates were randomly selected for identification based on partial sequences of 16S rRNA gene. Six isolates were found belong to the genus Streptomyces, two isolates belong to the genus Micromonospora and two isolates were identified as Rhodococcus spp. Conclusion, significance and impact of study: These findings revealed the potential of mangrove sediment of Tanjung Lumpur as an important source of actinomycetes with biosynthetic capabilities which might be beneficial to pharmaceutical industries.